Gender dynamics in hand hygiene practices: A survey in a specialized dermatological Scientific Institute for Research, Hospitalization and Health Care - Altamura, Gerardo; Laurenti, Patrizia; Alizadeh, Aurora Heidar; Raspolini, Gian Marco; Facchiano, Antonio; Virgili, Rosamaria; Nurchis, Mario Cesare; Raponi, Matteo; Cavarra, Marco; Panebianco, Annarita; Damiani, Gianfranco (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. A high adherence to hand hygiene procedures is regarded as cost-effective for preventing healthcare-associated infections. How important it is perceived by healthcare workers may determine the level of adherence to recommendations. This survey aimed at investigating perceptions, practices, and gender dynamics surrounding hand hygiene among healthcare professionals. Study design. This study followed a cross-sectional design, involving a questionnaire administered only once to each participant.Methods. The study was set in a dermatological Scientific Institute for Research, Hospitalization and Healthcare (SIRHHC) in Italy. An internet-based survey was made available to every SIRHHC’s healthcare worker for two months of 2024. Surveyed population consisted of healthcare professionals involved in patient care within the SIRHHC, including physicians, nurses, and other healthcare staff. The questionnaire was based on the World Health Organization Hand Hygiene Self-Assessment Framework 2010 and involved both open-ended questions and Likert-scale items. Descriptive statistics and qualitative analyses were used to identify themes and quotes related to hand hygiene. To examine the relationship between the percentage of inpatients who will suffer from a healthcare-associated infection and predictor variables, a generalized linear model was fit. Tests were conducted to assess the robustness of results.Results. Answers from 172 respondents, predominantly nurses (66.86%) and female workers (69.6%), were analyzed. Training emerged as a critical determinant of awareness, with participants reporting higher perceived compliance (86.98%) than general compliance rates (77.52%). However, workload pressures and perceived effort required for adherence (rated 5.70/7) were identified as barriers to consistent practice. Institutional support for hand hygiene, reflected in training initiatives and leadership prioritization (rated 3.87/4), was strong, yet patient involvement remained underutilized (rated 4.55/7). While gender differences in beliefs about healthcare-associated infections (HCAIs) were not statistically significant, the high representation of women highlighted their pivotal role in infection prevention and the potential for leadership in hygiene promotion.Conclusions. This study provides actionable insights into improving hand hygiene practices and fostering a culture of safety within healthcare settings.